Emerging nano-strategies against tumour microenvironment (TME): a review - Debojyoti Mandal; Kriti Kushwaha; Jeena Gupta (Elsevier, 2023)
The non-cancerous cells and substances found in tumours, including the chemicals they create and release, are referred to as the tumour microenvironment. Carcinogenesis relies on the tumour microenvironment because it contains tumour cells that communicate with neighbouring cells via the circulatory and lymphatic systems. During all stages of carcinogenesis, non-malignant cells in the tumour microenvironment promote unchecked cell proliferation. Changes in the genetics and epigenetics of tumour cells and the rearrangement of TME components, which happen when these two things work together, affect the formation and growth of tumours. Tissue-specific exchanges between tumour cells and their surroundings are critical to understanding the underlying mechanism. With the tremendous advancements in nanomedicine, TME modulation has made significant strides lately. Drug distribution using nanotechnology has a number of benefits, including increased circulation time, cargo delivery to the appropriate location, enhanced bioavailability, reduced toxicity, etc. High interstitial pressure and dense stroma prevent the extravasation and uniform distribution of nanocarriers in TME, but leaky vasculature, acidic, and hypoxic circumstances of TME aid in the aggregation of customised nanoparticles. The goal of the review is to look into the idea of the tumour microenvironment by doing a critical analysis of past research. By briefly analysing stromal components, therapeutic opportunities, and limitations provided by TME for nanoparticulate drug delivery, this paper primarily analyses the potential of nanotherapeutics in targeting TME. Additionally, updated details on TME remodelling techniques for better drug delivery and precise targeting of particular stromal components are provided.